2013
DOI: 10.1590/s1414-462x2013000400003
|View full text |Cite
|
Sign up to set email alerts
|

Tabagismo: abuso físico parental e fatores associados entre pacientes dos ambulatórios do Hospital Universitário Júlio Muller, Cuiabá (MT), 2013

Abstract: Com o objetivo de analisar a associação do tabagismo e aspectos familiares, entre os quais o abuso físico parental, foi realizado um levantamento epidemiológico em 604 usuários dos ambulatórios do Hospital Universitário Júlio Müller da Universidade Federal de Mato Grosso, na faixa etária de 18 a 85 anos, de março a agosto de 2013. Aplicado questionário sobre os aspectos biossociodemográficos, familiares e tabagismo, sendo este definido conforme os critérios do Ministério da Saúde. Utilizou-se a análise bivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…According to a study conducted in Brazil, a high educational level of the pregnant woman and her partner is more prone to free cigarette families. Women with low schooling have less control of smoking in the family environment and are more likely to passive smoking (20) . In fact, the health-disease process is a complex reality, as proposed by the Labonte's model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a study conducted in Brazil, a high educational level of the pregnant woman and her partner is more prone to free cigarette families. Women with low schooling have less control of smoking in the family environment and are more likely to passive smoking (20) . In fact, the health-disease process is a complex reality, as proposed by the Labonte's model.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that the smoking habit in the families of the pregnant women interviewed is something that lasts for generations, seen naturally in the norms of family life. By studying the prevalence of smoking and its association with relationships established in families, it was observed that when tobacco consumption was indiscriminate inside and outside the family environment, often, regardless of the presence of children, the percentage of smokers among the members of the family was high (20) . Thus, it is clear the need for prenatal care to operate from the recognition of the pregnant woman as a subject endowed with self-will, but with limitations in the expression of their autonomous decisions as a consequence of their belonging to a family context that naturally faces the habit of smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation